System Development for Multistage Adaptive Testing with Feedback in O-NET for The Subject of Grade 12 English Language by Nhabhat Chaimongkol - Chaimongkol, Nhabhat (Dusit Thani College Journal, 2020)
Computerized adaptive testing (CAT) is a system that uses a computer process to select items that match the ability of examinees. The classical CAT still has some limitations in ability estimation. Therefore, researchers have developed multistage adaptive testing (MST) to overcome the limitations of the classical CAT. This research develops MST for the preparation of Ordinary National Educational Test (O-NET) in English. This is because most students are unable to pass the O-NET exam in English. The results found that the system consists of 5 components 1) initial stage 2) ability estimation 3) item selection 4) stopping criteria and 5) feedback report, contained both the raw score and ability level of each examinee. Finally, the quality of the system is evaluated by experts using standard evaluation and by students using user satisfaction. The results show that the system is of high quality in every dimension and the overall user satisfaction is quite good.